(3eNJUQ aj UfGYI GdWHs - (3aNQ GdOjf CHj fUQ eMeO Hf eMeO Hf Ydj GdNLfOj, aNQ GdedI,J (B703 (3g` s ((3eMeO Hf bWH GdWHjH s)
(3ChdgG (B:s
(3hHYO (B: (3agPG eNJUQaj UfGYI GdWH CdaJg dHYV GdeJYdejf hChOYJg ahGFO ZQjHI haQGFO YLjHI, hde JhLO ai CcKQ GdcJH GdeUfaI aj gPG Gdaf s
(3BNQgG (B:s
(3hdjcf gPG BNQ cdGefG aj gPG GdoeNJUQ aef MaX agh Ndjb HGdEUGHI aj CYeGdg hHGdJMbjb aj CbhGdg s
(3Vef eLehY , JQJjHgG (B: (3ef U (B478 - (3U(B510s
(3GfXQg eY GdeQTO HQbe (B730s
(3bQf GdfSN (B:s
(3GdbQf GdJGSYs
(3GdJhKjbGJ GdeQLYjI (B:s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA WH (B- (3bSe GdcGH GdKGfj (B- (3U (B223 s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3GdWHs